Evolution constant change and common threads - Sean B. Carroll, lecturer; David M. Kingsley, lecturer (Howard Hughes Medical Institute, 2006)
"Join two leading biologists on an exploration of how key developmental genes, natural selection, and time fuel the evolutionary process"--Cover.